Dust storm 'hot spots' and Transport Pathways Affecting the Arabian Peninsula. (1st November 2022) - Al-Hemoud, Ali; Al-Dashti, Hassan; Al-Saleh, Abeer; Petrov, Peter; Malek, Mariam; Elhamoud, Ebrahim; Al-Khafaji, Sarhan; Li, Jing; Koutrakis, Petros; Doronzo, Domenico; Middleton, Nick
Abstract: The Arabian Peninsula (AP), the largest peninsula in the world, contains 'hot spot' areas for intensive dust storms. Dust sources outside the AP can also represent 'hot spots' that heavily impact the AP. This study explores the source and transport pathways of severe dust storm events over the AP over nine years (2010–2018) using MODIS Aqua and Terra satellites (0.25–0.5 km/pxl resolution) combined with the HYSPLIT model and synoptic meteorology. The study identified ten dust source 'hot spots' that affect the AP; two are local (within the AP) and eight are regional (outside the AP). The identified local dust sources were (1) the Empty Quarter and (2) the Mesopotamian flood plain in southern Iraq, while the regional dust sources were (3) the Syria-Iraq border, (4) Hamun-e Jaz Murian, (5) Coastal desert of Iran, (6) Seistan basin ephemeral lakes, (7) Hamun-e Mashkel, (8) Thar desert of Rajasthan, (9) Nile River basin, and (10) Wadi Langeb Tokar Delta. To the best of our knowledge, this is the first study to investigate the emission and transport of dust storms over the AP at the local and regional/subcontinental levels using medium-high resolution remote sensing. This study has important implications for the international community and the multilateral environmental agreements related to desert dust. Highlights: The study explored the source 'origin' and transport pathways of recurring severe dust storms over the Arabian Peninsula. Ten dust storm sources 'hot spots' affect the Arabian Peninsula. Two dust storm sources are local (The Empty Quarter and the Mesopotamia). Eight dust storm sources are regional/subcontinental. High resolution MODIS Aqua and Terra are effective in delineating dust storms' origin and transport.